2 Kor 1, 15-16: Pawłowy plan wizyt w Koryncie i jego realizacja - Rakocy, Waldemar (The Biblical Annals, 2017)
The subject of the article is the information in II Cor 1,15-16, according to which Paul did not put into effect the visit to the Corinthians that he had foretold. In the contemporary biblical studies there are two fundamental opinions on the degree to which the visit was not executed: 1) the Apostle did not make the foretold visit at all; 2) he made only half of it, that is from Corinth he went to Macedonia, but he did not return to Corinth as he had announced earlier. A verification of the two opinions leads to the conclusion that the latter one meets with objections that raise serious doubst; the former one does not create such difficulties and seems more plausible.